The Contributing Dimensions and Elements of Maqasid Sharia to the Well-Being in Pesantren - Darihan Mubarak (Muslim Education Review, 2025)
This research aims to identify the factors that contribute to well-being in Islamic boarding schools (pesantren) using the six-dimensional Maqasid al-Sharia approach, specifically by exploring the key elements in the dimensions of the well-being of maqasid sharia from a pesantren’s perspective. This research uses a mixed-method study. The qualitative analysis was employed through interviews with kiai, ustadz/ustadzah, supervisors, and pesantren owners. Quantitative research was carried out by distributing online surveys, and SPSS was used to determine the internal consistency and the most critical dimensions based on Cronbach’s alpha value and mean score. Through in-depth interviews, it was found that there are 56 elements of well-being in the six dimensions of maqasid sharia. The author also found that safeguarding religion and safeguarding intellect are the two most vital dimensions in pesantren. However, all six dimensions play a critical role in supporting the well-being of pesantren. In practical terms, this model provides policy makers and leadership at the pesantren level with guidance on implementing holistic well-being through curriculum development, character building and organizational policy. Methodologically, the study illustrates the usefulness of qualitative conceptualization, supplemented by quantitative prioritization, in developing culturally grounded models of Islamic well-being. Further studies are recommended to confirm and extend the model across other Islamic educational settings.